Microbial aerobic denitrification dominates nitrogen losses from reservoir ecosystem in the spring of Zhoucun reservoir - Zhou, Shilei; Zhang, Yiran; Huang, Tinglin; Liu, Yanfang; Fang, Kaikai; Zhang, Chunhua (The Science of the total environment, 2019)
The mechanism and factors influencing nitrogen loss in the Zhoucun reservoir were explored during the spring. The results showed that the nitrate and total nitrogen concentration decreased from 1.84 ± 0.01 mg/L and 2.34 ± 0.06 mg/L to 0.06 ± 0.01 mg/L and 0.48 ± 0.09 mg/L, respectively. Meanwhile, the nitrate and total nitrogen removal rate reached 97.02% ± 0.25 and 79.38% ± 3.32, respectively. Moreover, the abundance of nirS gene and aerobic denitrification bacteria increased from 1.04–3.38 × 103 copies/mL and 0.71 ± 0.22 × 102 cfu/mL to 5.36–5.81 × 103 copies/mL and 8.64 ± 2.08 × 103 cfu/mL, respectively. The low MW fractions of DOM (<5 kDa) increased from 0.94 ± 0.02 mg/L in February to 1.51 ± 0.09 mg/L in April. E3/E4 and absorption spectral slope ratio (SR) showed that fulvic acid accounted for the main proportion with autochthonous characteristics. These findings were consistent with the fluorescence components and fluorescence characteristic indices based on EEM-PARAFAC. Meanwhile, the microbial metabolism activity increased significantly from February to April, which contributed to the cycle of nutrients within the reservoir water system. Moreover, the abundance of the bacterial species involved in denitrification (Exiguobacterium, Brevundimonas, Deinococcus, Paracoccus, and Pseudomonas) increased significantly. The relative abundance of KOs related to nitrogen metabolism, were initially increased and then decreased. Specifically, K02567 (napA) represented the main proportion of KOs related to denitrification. The abundance of napA-type denitrifying bacteria (Dechloromonas, Pseudomonas, Azospira, Rhodopseudomonas, Aeromonas, Zobellella, Sulfuritalea, Bradyrhizobium, Achromobacter, Enterobacter, Thauera, and Magnetospirillum) increased significantly during the period of nitrogen loss. Furthermore, the levels of nitrate, T, DO, and AWCD were the most important factors affecting the N-functional bacteria composition. The systematic investigation of the nitrogen loss would provide a theoretical foundation for the remediation of the water reservoir via aerobic denitrification in the future. [Display omitted] •Microbial aerobic denitrification dominates nitrogen loss of water column in the spring.•The abundance of nirS and aerobic denitrification bacteria increased obviously.•The abundance of N-functional bacteria and napA-type denitrification bacteria both exhibited obvious increase process.